Keefektifan Konseling Kelompok Dengan Teknik Extinction Dalam Mereduksi Kenakalan Remaja - Herman Herman; Manah Rasmanah; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "Effectiveness of group counseling using techniques Extinction to reduce juvenile delinquency”. This research is motivated by because juvenile delinquency is a problem that occurs in many circles students are good in their living environment, if not minimized it wil be have a very significant impact on life. So therefore With this research, it is hoped that a bette environment can be created safe, stable and positive for teenagers in Kayuagung District and in the region others with similar problems to reduce the level of juvenile delinquency This requires a special technique to be used in handling it, one of them is by using the extinction technique Purpose of the research This is to determine the effectiveness of Group Counseling with Extinction Techniques in Reducing Juvenile Delinquency. The type of research used is quantitative with experimental methods, while the design used in This research is a quasi research that uses a sample of 10 teenagers Kayuagung District. Data collection techniques use questionnaires, observation and documentation. The data analysis technique uses the Wilcoxon test. Research result This shows that first, the results of the pretest level of juvenile delinquency are in the high category with M=77.20 while the posttest results are in the category low with M=73.80. The results of the analysis using the Wilcoxon test show The resulting sig value is = 0.005. So it can be concluded that counseling groups using the Extinction technique are effective in reducing juvenile delinquency.